APPROXIMATE ANALYTICAL APPROACH FOR NONLINEAR BOUNDARY LAYER THIN FILM FLOW AND HEAT TRANSFER ANALYSIS OVER A STRETCHING SURFACE - ALI REHMAN (UNIVERSITI MALAYSIA TERENGGANU, 2022)
The aim of this thesis is to construct mathematical model for nonlinear differential equation of boundary layer flow over a stretching surface and find its approximate analytical solution. The analytical approximate method named Optimal Homotopy Asymptotic Method (OHAM) is used for the approximate analytical solution. The convergence of the OHAM for particular problems is also discussed. The series solution for both velocity and temperature profiles are calculated by using OHAM. It is an influential approximate analytical technique and various researchers employed OHAM-BVPh 2.0 technique for several flow problems. After implementing the boundary layer approximation on thin film flow model equations, we obtain a set of partial differential equations (PDEs). These equations were transformed into a set of non-dimensional nonlinear ordinary differential equations (ODEs) through suitable self-similar alteration method. The dimensional form of coupled nonlinear ODEs one for velocity and other for temperature were obtained through OHAM-BVPh 2.0 package. Furthermore, the impact of the model factors which are involved in velocity and temperature profiles are displayed numerically and graphically. Also the flow problem is discussed geometrically. The skin friction coefficient and Nusselt number is discussed in table form. In 1995, in the ASME Winter Annual Conference, Choi introduced the term of nanofluid.